2007
DOI: 10.1007/s11307-007-0097-0
|View full text |Cite
|
Sign up to set email alerts
|

Intrapatient Comparison of 2-Deoxy-2-[F-18]fluoro-d-glucose with Positron EmissionTomography/Computed Tomography to Tc-99m Fanolesomab (NeutroSpec) for Localization of Infection

Abstract: FDG-PET/CT is superior to Tc-99m fanolesomab for detecting and localizing sites of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…99m Tc-fanolesumab is a murine anti-CD15 IgM monoclonal antibody labeled with 99m Tc which was approved for imaging of equivocal cases of acute appendicitis and was in trials for use in imaging osteomyelitis and occult infection (6,90,104,162 (90). Shortly after infusion, a transient drop in the absolute neutrophil number has been observed, but no infectious complications have been attributed to Tc-fanolesumab (102,104).…”
Section: Monoclonal Antibodies For Imagingmentioning
confidence: 99%
“…99m Tc-fanolesumab is a murine anti-CD15 IgM monoclonal antibody labeled with 99m Tc which was approved for imaging of equivocal cases of acute appendicitis and was in trials for use in imaging osteomyelitis and occult infection (6,90,104,162 (90). Shortly after infusion, a transient drop in the absolute neutrophil number has been observed, but no infectious complications have been attributed to Tc-fanolesumab (102,104).…”
Section: Monoclonal Antibodies For Imagingmentioning
confidence: 99%
“…The difference in the diffusion of water molecules among tissues enables DW-MRI to detect malignant tumors and differentiate them from benign masses ( 12 ). Previous studies have shown that DW-MRI is comparable with PET/CT in detecting malignant lesions ( 13 15 ). Numerous studies reported that DW-MRI provided more accurate delineation for a number of cancer types, including prostate, head and neck, and cranial tumors ( 16 18 ).…”
Section: Introductionmentioning
confidence: 97%